Evaluation of Lipid Profile in Premature, Near-term and Term Newborn Infants - Kurrey, Dr. Ram Manohar; J. Lall, Dr. Kavita; Chandrakar, Dr. Karan Singh (International Journal of Innovative Research in Medical Science, 2017)
In this study we evaluate the activity of lipid profile in premature, near term and term neonates. A total number of 68 newborn infants were selected for this study. They were delivered normally, or by caesarean section, and their gestational age was included. The infants with congenital anomalies or those, whose mothers had medical problems, were excluded from the study. The gestational age was determined according to the date of the last menstrual period, or the early ultrasound in 20 weeks of gestation. All the information related to the newborns and their mothers were recorded in the prepared forms. Following the delivery, blood samples were taken from the umbilical cord immediately, and were separated after clotting, for at least 30 min at room temperature. Serum was stored at 4°C to -80C for a maximum of 2 days, prior to the analysis. Total cholesterol, triglycerides and HDL were analyzed by enzymatic method using auto-analyzer. Serum Total Cholesterol estimated by enzymatic kit method, Triglyceride estimated by bioluminescent assay method and HDL-cholesterol estimated by phasphotungstate precipitation method manufactured by ERBS Transasia. LDL-C and VLDL-C calculated by Friedewald formula. The three groups were significantly different, regarding the means of age, weight and cholesterol and LDL-C level, whereas no significant difference was observed concerning the level of triglyceride and HDL-C,. Gender has no effect on the level of cholesterol, triglyceride, HDL-C and LDL-C in the total population and in all subgroups (P value more than 0.05). On the basis of present study we assume that the cholesterol level was higher in those with prematurity and pre-term delivery, and is also inversely correlated with the infant’s birth weight. Therefore, we believe that monitoring, observation and early-lifestyle modifications may decrease the severity of atherosclerosis in the vessels in adulthood. This study says, it is evident that the total cholesterol and LDL cholesterol in premature and near term neonates was higher than a term neonates ; triglyceride and VLDL were higher in term neonates as compared to near term neonates. Fall in HDL was significantly observed in premature neonates than term neonates and near term neonates but no significance found in term and near term neonates.